Porous carbon material for capturing palladium ions in highly-radioactive acid waste liquid and preparation method of porous carbon material

By using glucose and melamine nitrogen/oxygen/sulfur doped porous carbon material, the problem of insufficient stability in the existing adsorbent in high acidity and high radioactive environment and low selection of pyrada adsorption have been solved. The effects of strong ions with strong sex and reduced production costs.

CN119327423AActive Publication Date: 2025-01-21NORTHWEST INST OF NUCLEAR TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411746233.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-01-21
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

The existing adsorbent materials are insufficient in high acidity and high radioactive environments, and have poor adsorption selectivity for palladium ions, making the preparation process complex and costly.

Method used

The glucose and melamine are used as the raw material. The polynomotic carbon material doped by the high -pressure reaction and gradient heating activation of nitrogen/oxygen/sulfur is improved to improve its stability in high acidity and high radioactive environment and the adsorption selectivity of pyradic ions.

Benefits of technology

It achieves efficient and selective capture of palladium ions in high-level acidic waste liquid, has good stability and durability, has a simple process, low cost, and is easy for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119327423A_ABST
    Figure CN119327423A_ABST
Patent Text Reader

Abstract

The invention discloses a porous carbon material for capturing palladium ions in highly-radioactive acid waste liquid and a preparation method of the porous carbon material. Glucose and melamine are used as a carbon source and a nitrogen source respectively, a nitrogen / oxygen co-doped carbon precursor is prepared through a hydrothermal reaction, then the precursor, an activating agent and a sulfur-containing co-activating agent are subjected to gradient heating activation, and the nitrogen / oxygen / sulfur co-doped porous carbon material is obtained. The porous carbon material disclosed by the invention has the characteristics of high nitrogen / oxygen / sulfur atom ratio, high mesoporous ratio, large specific surface area, wide pore size distribution range and the like, and has the advantages of high efficiency, high capacity, high selectivity and good stability when being used for capturing palladium ions in highly-radioactive acid waste liquid; in addition, the preparation method of the porous carbon material has the advantages of low cost, simplicity in operation and the like, and industrial production is easy to realize.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of porous materials, and in particular relates to a porous carbon material for capturing palladium ions in high-acid waste liquid and a preparation method thereof. Background Art

[0002] The precious metal palladium is widely used in catalysis, sensing, electronic devices, decoration and other aspects due to its superior physical and chemical properties such as high temperature resistance, oxidation resistance, corrosion resistance, high catalytic activity and strong coordination ability. However, the concentration of palladium in the earth's crust is low, ranging from 0.1 to 3 ng / g, and is unevenly distributed around the world. In recent years, driven by the unprecedented growth of the mobile phone and automobile industries, the demand for palladium has grown rapidly, and the shortage of palladium is expected to become more serious. Therefore, separating and recovering palladium from waste resources can not only alleviate the shortage of palladium, but also greatly reduce environmental pressure. The high-level acidic waste generated by the spent fuel cycle process contains a considerable amount of palladium. Extracting palladium from high-level acidic waste not only helps to enrich the limited palladium resources, but also solves the difficult problems of glass-solidified nuclear waste storage technology.

[0003] At present, methods such as solvent extraction, precipitation, membrane separation, electrochemical method and adsorption have been applied to extract palladium from high-level acidic waste liquid. Among them, the adsorption method is widely used in the field of metal separation and enrichment due to its advantages such as low cost, easy operation and environmental friendliness. The key to the adsorption method is the adsorbent material. The adsorbents that adsorb and capture palladium from high-level acidic waste liquid mainly include: anion exchange resin, ligand-modified mesoporous silica, metal organic framework materials and porous organic polymers. However, high-level acidic waste liquid usually contains many metal ions, and has high radioactivity and high acidity. The above-mentioned adsorbent materials have insufficient stability and durability in high acidity and high radioactivity environments, and the adsorption selectivity for palladium ions is not strong. For example, anion exchange resins and ligand-modified silica are prone to leaching of surface active species in high-level acidic wastewater (J. Environ. Chem. Eng., 2024, 12, 112402.; RSC Adv., 2017, 7, 30815-30838.); metal-organic framework materials have poor stability in high-level acidic waste liquid environments (Green Chem. Eng., 2024, 5, 187-204.; Chemosphere, 2024, 349, 140729.); porous organic polymers require expensive organic monomers and a large amount of toxic and harmful organic solvents during the preparation process, and the synthesis steps are relatively complicated (Angew. Chem. Int. Ed., 2023, 62, e202305225.).

[0004] Compared with the above-mentioned adsorbent materials, porous carbon materials have the advantages of wide sources, low prices, high specific surface area, high porosity, adjustable pore size, good chemical stability and thermal stability. Porous carbon materials are widely used as adsorbent materials. However, porous carbon materials mainly have the problem of poor selectivity. In order to improve the adsorption selectivity of porous carbon materials, the literature (ACS Appl. Mater. Interfaces, 2023, 15, 40088-40099.) prepared sulfur-doped porous carbon materials, which have good adsorption selectivity for precious metal silver ions. Patent CN114177920A uses anthraquinone-1,8-disulfonic acid dipotassium as raw material to prepare sulfur-doped carbon materials, which have good adsorption capacity and adsorption selectivity for gold ions under high acid conditions; However, due to the protonation of sulfur atoms under high acid conditions, the coordination and complexing ability of sulfur atoms doped on the surface of porous carbon materials with palladium ions is significantly weakened. In addition, patent CN113893821A uses 2-aminothiazole as a carbon source, and obtains a nitrogen-sulfur doped porous carbon material through pyrolysis activation. However, the process of using 2-aminothiazole as a carbon source still has the problem of high raw material prices. In addition, the nitrogen-sulfur doped porous carbon material still cannot meet the requirements of capturing palladium ions in high-acid waste liquid. Summary of the invention

[0005] The purpose of the present invention is to solve the defects of various adsorbent materials used for capturing palladium ions in high-acid waste liquid, such as insufficient stability and durability in high-acidity and high-radioactivity environments, insufficient adsorption selectivity for palladium ions, or complex preparation process and high price of the adsorbent materials, and to provide a porous carbon material with simple preparation process, low cost, high selectivity, strong durability and stability for capturing palladium ions in high-acid waste liquid, and a preparation method of the porous carbon material.

[0006] The porous carbon material for capturing palladium ions in high-level acidic waste liquid provided by the present invention is prepared by the following method:

[0007] Step 1: After glucose and melamine are uniformly dispersed in pure water, they are transferred to a high-pressure reactor and reacted at 120-200°C for 12-24 hours; after the reaction is completed, the precipitate is cooled to room temperature, and washed with pure water and ethanol until the filtrate is colorless, and then dried to obtain a black nitrogen / oxygen co-doped carbon precursor.

[0008] Step 2: Disperse the nitrogen / oxygen co-doped carbon precursor, activator and co-activator evenly in pure water, dry and grind evenly, then place the evenly ground mixture in a high-temperature tube furnace, and activate it in an inert atmosphere by a gradient heating method. The gradient heating method is: first increase the temperature from room temperature to 400-500°C, keep it warm for 30-40 minutes, then continue to heat it to 600-650°C, keep it warm for 30-40 minutes, and finally increase the temperature to 700-900°C, keep it warm for 1-2 hours; after the activation is completed, immerse the activated product in a hydrochloric acid aqueous solution to remove impurities, and finally dry it to obtain the porous carbon material.

[0009] In the above step 1, the mass ratio of glucose to melamine is preferably 1:0.5-5.

[0010] Furthermore, in step 1, the reaction is preferably carried out in a high pressure reactor at 160-180° C. for 12-24 hours.

[0011] In the above step 2, the mass ratio of the nitrogen / oxygen co-doped carbon precursor, activator and co-activator is preferably 1:1-5:0.1-0.5. The activator is potassium hydroxide, and the co-activator is any one of ammonium hydrogen sulfate or ammonium sulfate.

[0012] Furthermore, in step 2, the gradient heating method is preferably: firstly, heating from room temperature to 450°C, keeping the temperature for 30 minutes, then continuing to heat to 650°C, keeping the temperature for 30 minutes, and finally heating to 700-800°C, keeping the temperature for 1 hour. The gradient heating rate is preferably 3-8°C / min.

[0013] In the above step 2, the inert atmosphere is any one of nitrogen or argon.

[0014] The porous carbon material provided by the present invention has a nitrogen doping amount of 5wt% to 15wt%, an oxygen doping amount of 10wt% to 20wt%, and a sulfur doping amount of 1wt% to 5wt%.

[0015] The porous carbon material provided by the present invention can be used to selectively capture palladium ions in highly radioactive acidic waste liquid. The HNO3 concentration in the highly radioactive acidic waste liquid is 1-6 mol / L, and the Pd(II) concentration is 1 ng / L-100 mg / L.

[0016] Furthermore, the high-level acidic waste liquid also contains any one or more metal ions of Li(I), Na(I), K(I), Mg(II), Co(II), Zn(II), Cu(II), Pb(II), Ba(II), Ni(II), Ca(II), Mn(II), Cd(II), Al(III), Cr(III), Nd(III), Fe(III), Ce(III), La(III), Ru(III), Ti(IV), Zr(IV), Nb(V), and Mo(VI).

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] The porous carbon material of the present invention has the characteristics of high nitrogen / oxygen / sulfur atom ratio, high mesopore ratio, large specific surface area, wide pore size distribution range, etc. It is used for capturing palladium ions in highly radioactive acidic waste liquid and has the advantages of high efficiency, high capacity, high selectivity and good stability, overcoming the problems of low efficiency, small capacity, poor selectivity and poor stability of previous solid-phase capture agents; in addition, the preparation method of the porous carbon material of the present invention has the advantages of low raw materials, simple process, etc., and is easy to realize industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 3 is a scanning electron microscope image of the porous carbon material prepared in Example 1.

[0020] Figure 2 It is a bar chart of the content of each element component of the porous carbon material prepared in Example 1.

[0021] Figure 3 This is the infrared spectrum of the porous carbon material prepared in Example 1.

[0022] Figure 4 is N2 adsorption-desorption isotherm curve and pore size distribution diagram of the porous carbon material prepared in Example 1.

[0023] Figure 5 This is a graph of the Pd(II) adsorption capacity of the porous carbon material prepared in Example 1 under different acidity conditions.

[0024] Figure 6 Graph showing the Pd(II) adsorption capacity of the porous carbon material prepared in Example 1 before and after high-energy ray irradiation.

[0025] Figure 7 This is a graph of the Pd(II) adsorption selectivity of the porous carbon material prepared in Example 1.

[0026] Figure 8 Graph showing the Pd(II) adsorption cycle stability and durability of the porous carbon material prepared in Example 1. DETAILED DESCRIPTION

[0027] The technical scheme of the present invention is described clearly and completely below in conjunction with the accompanying drawings and embodiments. The described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Example 1

[0029] Step 1: Dissolve 6 g of glucose and 3.25 g of melamine in 40 mL of pure water, then transfer them to a 100 mL high-pressure reactor and stir the reaction at 180 ° C for 12 hours under closed conditions; after the reaction is completed and cooled to room temperature, collect the precipitate by suction filtration, and wash it with pure water and ethanol until the filtrate is colorless, and then dry it in an oven at 80 ° C for 12 hours to obtain a black nitrogen / oxygen co-doped carbon precursor.

[0030] Step 2: Disperse and dissolve 2g of nitrogen / oxygen co-doped carbon precursor, 6g of potassium hydroxide and 0.2g of ammonium sulfate in 40mL of pure water, dry and grind them evenly at 80°C after stirring and dispersing them evenly, then place the evenly ground mixture in a high-temperature tube furnace and activate it in a nitrogen atmosphere by gradient heating. The gradient heating method is: at a heating rate of 5°C / min, first increase the temperature from room temperature to 450°C, keep it warm for 30min, then continue to increase the temperature to 650°C, keep it warm for 30min, and finally increase the temperature to 700°C, keep it warm for 1h. After the activation is completed, immerse the activated product in a 1mol / L hydrochloric acid aqueous solution to remove impurities, wash it and dry it at 80°C for 12h to obtain a nitrogen / oxygen / sulfur co-doped porous carbon material.

[0031] Depend on Figure 1 It can be seen that the porous carbon material obtained in this embodiment has an obvious porous honeycomb structure. Figure 2 It can be seen that the nitrogen doping amount in the obtained porous carbon material is 7.56wt%, the oxygen doping amount is 13.76wt%, and the sulfur doping amount is 1.70wt%. Figure 3 Medium 3660cm -1 The broad absorption band at 1654 cm is the vibration of OH and NH groups in the porous carbon material. -1 The absorption band that appears corresponds to the vibration of the C=C group, 1572 cm -1 The strong absorption bands at 1548 and 1040 cm-1 are attributed to the vibration of the C=O double bond. -1 The absorption band at 1120cm is attributed to the vibration of CN. -1 The absorption bands at 1083 and 663 cm are attributed to the vibration of CO. -1 The two absorption bands appearing at belong to the stretching vibration of S=O and CS. Figure 4 It can be seen that the isotherm curve of the obtained porous carbon material belongs to a mixed type of type I and type IV in the IUPAC classification. Under low pressure (0.0-0.1P / P0), the adsorption capacity of the porous carbon material increases sharply, indicating the presence of abundant micropores. Under medium pressure (0.4-0.8P / P0), an obvious H4-type hysteresis loop can be seen, indicating the presence of abundant mesopores in the material. In addition, when the relative pressure is close to 1.0, the rise of the adsorption curve indicates the presence of macropores in the material; that is, the porous carbon material prepared in this embodiment has a hierarchical pore structure of micropores / mesopores / macropores. The specific surface area calculated by the BET method is 1932m 2 g -1 The pore volume calculated by HK method is 0.86 cm 3 g -1 .

[0032] Example 2

[0033] Step 1: Dissolve 6 g of glucose and 6 g of melamine in 40 mL of pure water, then transfer them to a 100 mL high-pressure reactor and stir the reaction at 160 ° C for 24 hours under closed conditions; after the reaction is completed and cooled to room temperature, collect the precipitate by suction filtration, and wash it with pure water and ethanol until the filtrate is colorless, and then dry it in an oven at 80 ° C for 12 hours to obtain a black nitrogen / oxygen co-doped carbon precursor.

[0034] Step 2: Disperse and dissolve 2g of nitrogen / oxygen co-doped carbon precursor, 2g of potassium hydroxide and 0.3g of ammonium sulfate in 40mL of pure water, dry and grind them evenly at 80°C after stirring and dispersing them evenly, then place the evenly ground mixture in a high-temperature tube furnace and activate it in a nitrogen atmosphere by gradient heating. The gradient heating method is: at a heating rate of 5°C / min, first increase the temperature from room temperature to 450°C, keep it warm for 30min, then continue to heat it to 650°C, keep it warm for 30min, and finally heat it to 800°C, keep it warm for 1h. After the activation is completed, immerse the activated product in a 1mol / L hydrochloric acid aqueous solution to remove impurities, wash it and dry it at 80°C for 12h to obtain a nitrogen / oxygen / sulfur co-doped porous carbon material. The nitrogen doping amount in the porous carbon material is 8.48wt%, the oxygen doping amount is 11.77wt%, and the sulfur doping amount is 3.35wt%.

[0035] Example 3

[0036] Step 1: Dissolve 3g of glucose and 6g of melamine in 40mL of pure water, then transfer them to a 100mL high-pressure reactor and stir the reaction at 180°C for 24h under closed conditions; after the reaction is completed and cooled to room temperature, collect the precipitate by suction filtration, and wash it with pure water and ethanol until the filtrate is colorless, and then dry it in an oven at 80°C for 12h to obtain a black nitrogen / oxygen co-doped carbon precursor.

[0037] Step 2: Disperse and dissolve 2g of nitrogen / oxygen co-doped carbon precursor, 6g of potassium hydroxide and 0.2g of ammonium sulfate in 40mL of pure water, and after stirring and dispersing evenly, dry and grind it at 80°C, then place the evenly ground mixture in a high-temperature tube furnace, and activate it in a nitrogen atmosphere by gradient heating. The gradient heating method is: at a heating rate of 5°C / min, first increase the temperature from room temperature to 450°C, keep it warm for 30min, then continue to heat it to 650°C, keep it warm for 30min, and finally heat it to 750°C, keep it warm for 1h. After the activation is completed, immerse the activated product in a 1mol / L hydrochloric acid aqueous solution to remove impurities, wash it and dry it at 80°C for 12h to obtain a nitrogen / oxygen / sulfur co-doped porous carbon material. The nitrogen doping amount in the porous carbon material is 13.35wt%, the oxygen doping amount is 10.26wt%, and the sulfur doping amount is 2.12wt%.

[0038] Example 4

[0039] The nitrogen / oxygen / sulfur co-doped porous carbon material obtained in Example 1 was used to capture palladium ions in high-level acidic wastewater. The specific experiment is as follows:

[0040] 1. Effect of acidity on the performance of porous carbon materials in capturing palladium ions

[0041] 10 mg of porous carbon material was immersed in 50 mL of 40 mg L -1 Pd(II) in HNO3 solution (wherein the HNO3 concentrations were 0.5M, 1M, 2M, 3M, 4M, 5M, and 6M, respectively) was continuously shaken at 180rpm and 35°C for 8h to reach adsorption equilibrium. The solution was filtered and the Pd(II) concentration in the solution was determined by inductively coupled plasma-mass spectrometry, and its adsorption capacity was calculated. The results are shown in Figure 5 .Depend on Figure 5 It can be seen that with the increase of HNO3 concentration, the adsorption capacity of porous carbon materials for Pd(II) gradually decreased. When the HNO3 concentration was 0.5 M, the adsorption capacity was 112.8 mg g -1 When the HNO3 concentration reaches 6 M, the adsorption capacity is 51.4 mg g -1 .

[0042] 2. Effect of high-energy ray irradiation on the performance of porous carbon materials in capturing palladium ions

[0043] 1 g of porous carbon material was exposed to high-energy gamma rays at a dose rate of 1800 Gy h -1 , the total dose is 100 kGy. 10 mg of irradiated porous carbon material was immersed in 50 mL of 40 mg L -1 Pd(II) in HNO3 solution (where HNO3 concentration is 3M and 6M respectively), continuously shaken at 180rpm and 35℃ for 8h to reach adsorption equilibrium, the solution was filtered and the Pd(II) concentration in the solution was determined by inductively coupled plasma-mass spectrometry, and its adsorption capacity was calculated. At the same time, it was compared with the unirradiated porous carbon material. The results are shown in Figure 6 .from Figure 6 It can be seen that the adsorption capacity of Pd(II) on porous carbon materials remains almost unchanged before and after irradiation.

[0044] 3. Selective adsorption of different metal ions by porous carbon materials

[0045] 10 mg of porous carbon material was added into 50 mL of 3 M HNO3 solution of mixed ions (Pd(II), Li(I), Na(I), K(I), Mg(II), Co(II), Zn(II), Cu(II), Pb(II), Ba(II), Ni(II), Ca(II), Mn(II), Cd(II), Al(III), Cr(III), Nd(III), Fe(III), Ce(III), La(III), Ru(III), Ti(IV), Zr(IV), Nb(V), Mo(VI)), with the concentration of each ion being 10 mg L -1 ; The solution was continuously shaken at 180 rpm and 35 °C for 8 h to reach adsorption equilibrium. After filtering, the concentration of each ion in the solution was determined by inductively coupled plasma-mass spectrometry, and the adsorption capacity of each ion was calculated. The results are shown in Figure 7 .from Figure 7 It can be seen that the porous carbon material has a high adsorption selectivity for Pd(II) and can capture Pd(II) from highly radioactive acidic waste liquid containing 25 complex ions.

[0046] 4. Stability and durability of palladium ion capture by porous carbon materials

[0047] 10 mg of porous carbon material was immersed in 50 mL of 1 mg L -1 After continuous shaking at 180 rpm and 35 °C for 8 h to reach adsorption equilibrium, the solution was filtered and the Pd(II) concentration in the solution was determined by inductively coupled plasma-mass spectrometry, and its removal rate was calculated. At the same time, the porous carbon material was collected by centrifugation. -1HNO3 and 1 mol L -1 The collected porous carbon material was eluted with a thiourea mixed eluent to desorb the adsorbed Pd(II). After continuous shaking at 180rpm and 35°C for 12h to achieve complete desorption, the concentration of Pd(II) in the eluent was determined by inductively coupled plasma-mass spectrometry, and its desorption rate was calculated. The eluted porous carbon material was collected by centrifugation, washed with deionized water and anhydrous ethanol, and dried in a 60°C oven for 12h. The regenerated porous carbon material continued the above adsorption-desorption experiment cycle for 9 times. The results are shown in Figure 8 .from Figure 8 It can be seen that the porous carbon material has excellent cycle stability and durability for the capture of Pd(II).

Claims

1. A method for preparing a porous carbon material for capturing palladium ions in high-level acidic waste liquid, characterized in that: The preparation method comprises the following steps: Step 1: After glucose and melamine are uniformly dispersed in pure water, they are transferred to a high-pressure reactor and reacted at 120-200° C. for 12-24 hours; after the reaction is completed, the mixture is cooled to room temperature, the precipitate is collected, and washed with pure water and ethanol until the filtrate is colorless, and then dried to obtain a black nitrogen / oxygen co-doped carbon precursor; Step 2: uniformly dispersing the nitrogen / oxygen co-doped carbon precursor, activator and co-activator in pure water, drying and grinding the mixture uniformly, then placing the uniformly ground mixture in a high-temperature tube furnace, and activating it in an inert atmosphere by a gradient heating method, wherein the gradient heating method is: firstly heating from room temperature to 400-500°C, keeping the temperature for 30-40 minutes, then continuing to heat to 600-650°C, keeping the temperature for 30-40 minutes, and finally heating to 700-900°C, keeping the temperature for 1-2 hours; after the activation is completed, immersing the activated product in a hydrochloric acid aqueous solution to remove impurities, and finally drying to obtain the porous carbon material; The activator is potassium hydroxide, and the co-activator is ammonium bisulfate or ammonium sulfate.

2. The method for preparing a porous carbon material for capturing palladium ions in high-level acidic waste liquid according to claim 1, characterized in that: In step 1, the mass ratio of glucose to melamine is 1:0.5-5.

3. The method for preparing a porous carbon material for capturing palladium ions in high-level acidic waste liquid according to claim 1, characterized in that: In step 1, the reaction is carried out at 160-180° C. for 12-24 hours.

4. The method for preparing a porous carbon material for capturing palladium ions in high-level acidic waste liquid according to claim 1, characterized in that: In step 2, the mass ratio of the nitrogen / oxygen co-doped carbon precursor, the activator and the co-activator is 1:1-5:0.1-0.

5.

5. The method for preparing a porous carbon material for capturing palladium ions in high-level radioactive acid waste liquid according to claim 1, characterized in that: In step 2, the gradient heating method is: firstly, heating from room temperature to 450°C, keeping the temperature for 30 minutes, then continuing to heating to 650°C, keeping the temperature for 30 minutes, and finally heating to 700-800°C, keeping the temperature for 1 hour.

6. The method for preparing a porous carbon material for capturing palladium ions in high-level radioactive acid waste liquid according to claim 1, characterized in that: In step 2, the rate of the gradient heating is 3-8°C / min.

7. The method for preparing a porous carbon material for capturing palladium ions in high-level acidic waste liquid according to claim 1, characterized in that: In step 2, the inert atmosphere is any one of nitrogen or argon.

8. A porous carbon material for capturing palladium ions in high-level acidic waste liquid obtained by the preparation method according to any one of claims 1 to 7, wherein the nitrogen doping amount in the porous carbon material is 5wt% to 15wt%, the oxygen doping amount is 10wt% to 20wt%, and the sulfur doping amount is 1wt% to 5wt%.

9. Use of the porous carbon material according to claim 8 for capturing palladium ions in high-level acidic waste liquid, wherein the HNO3 concentration in the high-level acidic waste liquid is 1 to 6 mol / L and the Pd(II) concentration is 1 ng / L to 100 mg / L.

10. Use of the porous carbon material according to claim 9 for capturing palladium ions in high-level acidic waste liquid, characterized in that: The high-level acidic waste liquid also contains any one or more metal ions of Li(I), Na(I), K(I), Mg(II), Co(II), Zn(II), Cu(II), Pb(II), Ba(II), Ni(II), Ca(II), Mn(II), Cd(II), Al(III), Cr(III), Nd(III), Fe(III), Ce(III), La(III), Ru(III), Ti(IV), Zr(IV), Nb(V), and Mo(VI).

Citation Information

Patent Citations

  • Nitrogen and sulfur doped porous carbon material precious metal adsorbent and preparation method thereof

    CN113893821A

  • Modified mesoporous silica adsorbent and preparation method and application thereof

    CN105617979A

  • Nitrogen and sulfur codoped porous carbon material and preparation and application methods thereof

    CN108529619A

  • Method for preparing sulfur-nitrogen co-doped porous carbon material by taking hydroquinonesulfonic acid potassium salt as activating agent

    CN111943199A

  • Nitrogen-sulfur double-doped porous carbon material catalyst and preparation method thereof

    CN113649044A